Prevention of Postoperative Bleeding in Anticoagulated Patients Undergoing Oral Surgery: Use of Platelet Rich Plasma - Muhammad Usman Asif, Talha Tanveer, Sana Adeeba Islam, Nosheen Khawar, Muhammad Talal Huda, Ahmed Jawaid, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Anticoagulant therapy is essential for patients with various medical conditions. The use of anticoagulant medications is associated with a prolonged bleeding time. Platelet-rich plasma (PRP) contains a high concentration of platelets. PRP has been used to improve bone and soft tissue regeneration and lessen postoperative complications. Study design: It is a randomized controlled study conducted at DOW International Dental College, Karachi for the duration of six months from August 2022 to January 2023. Material and Methods: The study was done on 40 patients who visited tertiary care unit for duration of six months. There were 6 patients that belonged to the age group 40-50 years. 19 and 15 patients were in the age group 55-60 years and 60-65 years respectively. There were 14 males and 26 females included in our study. There were 72 extractions performed on these patients. Results: It was found that there were 4 patients who reported about hemorrhagic complications. There were two women that had hemorrhage linked to poor placement of platelet gel. One patient reported about hemorrhage related to severe formation of coagulum. Mild bleeding was observed in 13 patients. Conclusion: In conclusion the results of our trial suggest that PRP is a successful anticoagulant therapy that can be used for preventing any post-operative hemorrhagic complication among patients going through dental surgery, as PRP is easy to use, it has low cost and a good placement into residual alveolar bone, therefore it has better outcomes among patients. Keywords: postoperative bleeding, anticoagulant therapy and Platelet-rich plasma.